Efecto biocida de las concentraciones del extracto de Phaeophyta padina en carne de res para hamburguesa a diferentes temperaturas de conservación - Montesdeoca Rivera, María Lorena (2021)
The present research work aimed to establish the biocidal effect of the extract of brown algae (Phaeophyta padina), in different concentrations applied to hamburger beef, a completely randomized design per block (A x block) was used, the microbiological variables (mesophilic aerobes, E. coli) and physicochemical variables (pH, acidity, humidity) was evaluated. In the microbiological variable, the data obtained was analyzed, by means of a non-parametric test, with the kruskal-Wallis statistical test of independent samples; while, the physicochemical variables presented as a result, instability in the pH in the samples inoculated with the doses of protein extract T1 (0%), T2 (0.5%), T3 (1.0%) and T4 (1.5%) at 6 ° C, in turn, the treatments maintained at a temperature of 4 ° C, demonstrated the decrease in microbiological growth for mesophilic aerobes, indicating that the best optimal refrigeration temperature is 4 ° C.